The Study on Acute·Subacute Toxicity of Juglandis Semen Herbal-acupuncture(JsD). - Kang Kye-Sung; Kwon Gi Rok (Korean Pharmacopuncture Institute, 2001)
Objective: This study was purposed to investigate the acute·subacute toxicity of Herbal acupuncture with Juglandis Semen(JsD) in mice and rats. Methods: Balb/c mice were injected intraperitoneally with JsD for LD50 and acute toxicity test. Sprague-Dawley rats were injected intraperitoneally with JsD for subacute toxicity test. Results: The results obtained were summarized as follows; 1. LD50 was uncountable as could not find the expired of treat group. 2. The clinical signs and body weight changes of mice treated with 0.2cc, 0.4cc JsD were not affected during the acute toxicity test. 3. In acute toxicity test of serum biochemical values of mice, total protein was increased in treat-1 group, compared with normal group, and total cholesterol was increased in treat-2 group, compared with normal group.(P＜0.05) 4. In subacute toxicity test, main toxic syndrome was not found. 5. The body weight was decreased in treat-2 group, compared with normal group and relative liver weight was decreased in treat-1, 2 group, compared with normal group in subacute toxicity test.(P＜0.05) 6. In subacute toxicity test, WBC, MCH, MCHC were decreased in treat-2 group and RBC was increased in treat-2 group, compared with normal group in complete blood count test.(P＜0.05) 7. In subacute toxicity test, treat groups were not changed serum biochemical values of rats, compared with noraml group.(P<0.05) Conclusions: According to the results, Herbal-acupuncture with Juglandis Semen caused no toxicity.